2012
DOI: 10.3123/jemsge.34.171
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Ethylating Agents: Where Do the Thresholds for Mutagenic/Clastogenic Effects Arise?

Abstract: The dose response relationships for induction of micronuclei in bone marrow and for induction of lacZ mutations in liver, large intestine, and bone marrow were assessed in mice after treatment with ethyl methanesulfonate (EMS). The animals were treated orally at doses between 1.25 to 260 mg/kg for up to 28 days. Statistical analysis indicated that the dose response curves were well compatible with a thresholded relationship with apparent thresholds AE25 mg/kg/day. In contrast, no threshold was apparent for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Since all Salmonella strains used are NER deficient, the removal of alkylation lesions can therefore mainly be attributed to Ogt. Gocke et al have calculated the rate of successfully (error free) repaired DNA lesions by Ogt as a function of EMS concentration [Gocke et al, ]. In brief, following treatment with EMS dose–response curves for the Ames tester strains TA1535 (Ogt+/Ada+) and YG7104 (Ogt−/Ada+) were fitted by Gocke et al using a benchmark dose model (PROAST).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since all Salmonella strains used are NER deficient, the removal of alkylation lesions can therefore mainly be attributed to Ogt. Gocke et al have calculated the rate of successfully (error free) repaired DNA lesions by Ogt as a function of EMS concentration [Gocke et al, ]. In brief, following treatment with EMS dose–response curves for the Ames tester strains TA1535 (Ogt+/Ada+) and YG7104 (Ogt−/Ada+) were fitted by Gocke et al using a benchmark dose model (PROAST).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that the expression of Ada protein is weakly induced by alkylating agents [Vaughan and Sedgwick, ].Yamada et al have found that Ames tester strains lacking methyltransferases became highly sensitive towards mutagenic alkylating agents [Yamada et al, ]. Recently, Gocke et al calculated the rate of DNA lesions faithfully repaired by alkyltransferases in response to EMS treatment in S. typhimurium [Gocke et al, ]. The value of the calculated repair rate was approximately 100% at dose levels below the observed threshold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation